2012
DOI: 10.5665/sleep.1688
|View full text |Cite
|
Sign up to set email alerts
|

Heart Rate Variability Can Be Used to Estimate Sleepiness-related Decrements in Psychomotor Vigilance during Total Sleep Deprivation

Abstract: The ECG carries information about a person's vigilance state. Hence, HRV measures could potentially be used to predict when an individual is at increased risk of attentional failure. Our results suggest that HRV monitoring, either alone or in combination with other physiologic measures, could be incorporated into safety devices to warn drowsy operators when their performance is impaired.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
121
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(140 citation statements)
references
References 38 publications
(40 reference statements)
8
121
3
Order By: Relevance
“…Chua et al showed that RRI power density in the 0.02-0.08 Hz range correlated with psychomotor vigilance task (PVT) experiments with 40-hour profile [8]. PVT was originally developed as a measurement of sustained attention.…”
Section: Heart Rate Variability and Drowsinessmentioning
confidence: 99%
“…Chua et al showed that RRI power density in the 0.02-0.08 Hz range correlated with psychomotor vigilance task (PVT) experiments with 40-hour profile [8]. PVT was originally developed as a measurement of sustained attention.…”
Section: Heart Rate Variability and Drowsinessmentioning
confidence: 99%
“…However, the correlation between HR and KSS is stronger than the correlation between HR and VLD. It is well known from previous work that HR in beats per minute is decreasing with higher sleepiness (Chua et al 2012) and increasing with increasing mental workload (Mehler et al 2011). …”
Section: Resultsmentioning
confidence: 97%
“…All three frequency bands were normalized by the total power. In addition, a more detailed frequency analysis based on 0.02-Hz bins from 0.0 to 0.40 Hz was conducted, similar to the approach proposed by Chua et al (2012). The 0.02-Hz frequency bands were normalized by total power as well.…”
Section: Heart Rate Measuresmentioning
confidence: 99%
See 2 more Smart Citations